2020
DOI: 10.1111/nph.16666
|View full text |Cite
|
Sign up to set email alerts
|

Increased above‐ground resource allocation is a likely precursor for independent evolutionary origins of annuality in the Pooideae grass subfamily

Abstract: Summary Semelparous annual plants flower a single time during their 1‐yr life cycle, investing much of their energy into rapid reproduction. By contrast, iteroparous perennial plants flower multiple times over several years, and partition their resources between reproduction and persistence. To which extent evolutionary transitions between life‐cycle strategies are internally constrained at the developmental, genetic and phylogenetic level is unknown. Here we study the evolution of life‐cycle strategies in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 80 publications
(127 reference statements)
0
23
0
Order By: Relevance
“…This requires an understanding of the physiological and developmental basis of iteroparous perenniality in different environmental contexts, as well as an awareness of potential factors that might facilitate switches between annuality and perenniality in different clades. A recent study on Pooideae grasses inferred 51 independent shifts from the perennial to annual habit and demonstrated a link between the origin of annuality and an undefined precursor trait (Lindberg et al, 2020). Further investigation into the nodes of origin for the precursor trait(s) revealed that they correspond to an increase in belowground to aboveground biomass ratio, suggesting that changes in resource allocation are critical for the evolution of growth habit, and by extension in the engineering of more efficient crop grasses.…”
Section: Evidence For Released Constraint On Grass Flowering Evolutionmentioning
confidence: 98%
“…This requires an understanding of the physiological and developmental basis of iteroparous perenniality in different environmental contexts, as well as an awareness of potential factors that might facilitate switches between annuality and perenniality in different clades. A recent study on Pooideae grasses inferred 51 independent shifts from the perennial to annual habit and demonstrated a link between the origin of annuality and an undefined precursor trait (Lindberg et al, 2020). Further investigation into the nodes of origin for the precursor trait(s) revealed that they correspond to an increase in belowground to aboveground biomass ratio, suggesting that changes in resource allocation are critical for the evolution of growth habit, and by extension in the engineering of more efficient crop grasses.…”
Section: Evidence For Released Constraint On Grass Flowering Evolutionmentioning
confidence: 98%
“…1), showing that fast RGR is not a prerequisite for the evolution of annual life history. Instead, annuals evolve at a faster rate in lineages with a larger investment in shoot relative to root mass (Lindberg et al, 2020). The faster growth of C 4 than C 3 grasses is manifested as gigantism in the size of shoot phytomers, but with no change in shoot branching.…”
Section: Discussionmentioning
confidence: 99%
“…1), showing that fast RGR is not a prerequisite for the evolution of annual life history. Instead, annuals evolve at a faster rate in lineages with a larger investment in shoot relative to root mass (Lindberg et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Some perennial species are seasonally dormant while others stay green year round. Evolutionary transitions between annual and perennial growth modes have occurred numerous times during land plant evolution ( Friedman and Rubin, 2015 ; Lindberg et al, 2020 ). Perenniality is usually the ancestral trait and the annual growth mode is derived ( Friedman and Rubin, 2015 ).…”
Section: Introductionmentioning
confidence: 99%